Building a nation through translation: the contribution of Salazar’s speeches in English - Chumbo, Isabel (2021)
Nation-building is a complex process and can be accomplished in many ways. While the Portuguese 20th century dictatorship of Oliveira Salazar enforced the many traits that made this period what it is, it remains a fact that the regime concerned itself with external policies and with the image it created among other countries, especially within Europe. One of the forms of imposing this idea of a nation was naturally through propaganda or ‘soft power’. The aim of this presentation is to show how translated propaganda contributed to a specific image of Portugal abroad, mainly through the speeches of Salazar, during the period of 1930-1950. Over these two decades the regime commissioned a high amount of textual production in several European languages, this attitude of intense translation efforts being viewed as a clear propaganda tool in itself. The English language and the intention of creating a specific image of the country among the British politicians and policy-makers was the goal of this course of action. Throughout the work, this will be highlighted through the qualitative analysis of a corpus of 29 speeches by Salazar published in English, mainly in London through Faber & Faber, but also in Lisbon, through the National Propaganda Secretariat. These circulated in book form, but also as individual booklets published under the umbrella collection “Salazar says”. These translations were for British consumption only. The outcome of this analysis will not only shed light on how the regime wanted to be known to a British target audience but also provide information on how the translation process occurred and thus shaped the nation-building process during this time frame and context.